A Framework for Race‐Related Trauma in the Public Education System and Implications on Health for Black Youth. (2nd October 2019) - Henderson, Dawn X.; Walker, Larry; Barnes, Rachelle R.; Lunsford, Alexis; Edwards, Christen; Clark, Christopher
ABSTRACT: BACKGROUND: A combination of increased suicide in the past decade, documented high rates of anxiety and depression, and the preponderance of other behavioral and emotional regulation challenges place black youth at risk for school suspension and involvement in the juvenile justice system. Pointing to deficits in black youth and their families negates how forces of racism, whether unconscious or conscious, can disrupt well‐being. METHODS: A framework for race‐related trauma in the public education system illustrates the interplay between macro‐level forces, such as institutional and symbolic racism, and micro level forces of racism such as racial discrimination and violence. Identifying causal links between these forces and adverse academic and health outcomes for black youth can inform interventions and strategies to reduce race‐related trauma. RESULTS: The framework for race‐related trauma is a multi‐level analysis of racism and recognizes school districts facing economic restraints and school personnel turnover may face significant challenges in designing intervening strategies. CONCLUSION: The framework guides change effort towards improving school climate and culture through preparing school professionals to meet the diverse needs of youth, strengthening family and community collaboration, and tackling those policies and behaviors that exclude and disconnect black youth.